Formulasi dan Karakterisasi Fisik Lotion Berbasis Minyak Jojoba (Simmondsia chinensis) sebagai Pelembab Kulit - Valentina Girsang; Nindya Luksiana; Evi Elisabet Nangsat; Siti Nur Aisyah; Fifi Alfionita; Annisa Dian Rizky (PT. Hasba Edukasi Mandiri, 2026)
Jojoba oil (Simmondsia chinensis) is widely utilized as a natural ingredient in skincare product development due to its numerous dermatological benefits. Its flavonoid content acts as an antioxidant, contributing to skin protection against damage. This study aimed to evaluate the potential of jojoba oil in lotion formulations. Objective: To develop lotion formulations containing jojoba oil at concentrations of 0% (F0), 2.5% (F1), 7.5% (F2), and 12.5% (F3). Methods: This experimental study involved the formulation of lotions with varying concentrations of jojoba oil as the active ingredient, namely F0 (0%), F1 (2.5%), F2 (7.5%), and F3 (12.5%). The prepared formulations were evaluated for their physical properties, including organoleptic characteristics, pH, viscosity, homogeneity, and spreadability. Results: Among the tested formulations, F2 containing 7.5% jojoba oil demonstrated the most favorable characteristics. It exhibited a slightly viscous consistency, yellowish-white color, smooth texture, rose fragrance, homogeneous appearance, pH value of 8, viscosity of 1981.0 mPa·s, and spreadability within the acceptable range of 5–7 cm. Conclusion: Based on the physical evaluation tests (organoleptic properties, homogeneity, pH, viscosity, and spreadability), formulations F0 and F3 did not meet the pH requirements, while F0 and F1 failed to comply with the viscosity standards. Formulation F2 was the only formulation that satisfied all evaluated physical parameters.